2022
DOI: 10.1161/strokeaha.121.036564
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Plaque Composition and Morphology Among Symptomatic Patients With Mild-to-Moderate Carotid Artery Stenosis

Abstract: Background and Purpose: Incidence of ischemic stroke differs between men and women, with substantially higher rates in men. The underlying mechanism of this difference remains poorly understood but may be because of differences in carotid atherosclerosis. Using an in-depth imaging-based approach, we investigated differences between carotid plaque composition and morphology in male and female patients with stroke, taking into account differences in total plaque burden. Additionally, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Sex differences have been recognized in the risk of carotid atherosclerotic plaque (Iemolo et al, 2004;Hellings et al, 2007;Ota et al, 2010;Vrijenhoek et al, 2013;Li et al, 2021). A recent prospective cohort study conducted in patients with recent ischemic cerebrovascular events and mild-to-moderate carotid stenosis also demonstrated that men are more likely to have a high-risk vulnerable carotid plaque with intraplaque hemorrhage and lipid-rich necrotic core than women, no matter the total plaque burden (van Dam-Nolen et al, 2022). Our findings provide a plausible genetic basis for the sex difference in carotid plaque vulnerability.…”
Section: Discussionmentioning
confidence: 51%
“…Sex differences have been recognized in the risk of carotid atherosclerotic plaque (Iemolo et al, 2004;Hellings et al, 2007;Ota et al, 2010;Vrijenhoek et al, 2013;Li et al, 2021). A recent prospective cohort study conducted in patients with recent ischemic cerebrovascular events and mild-to-moderate carotid stenosis also demonstrated that men are more likely to have a high-risk vulnerable carotid plaque with intraplaque hemorrhage and lipid-rich necrotic core than women, no matter the total plaque burden (van Dam-Nolen et al, 2022). Our findings provide a plausible genetic basis for the sex difference in carotid plaque vulnerability.…”
Section: Discussionmentioning
confidence: 51%
“…Several lines of evidence link cardiovascular calcification to hyperlipidemia. In a recent study of patients with cerebrovascular symptoms, hypercholesterolemia was associated significantly with carotid artery calcification, especially in male patients [4 ▪ ]. Among patients with heterozygous familial hypercholesterolemia, those with physical signs of tendon xanthomas and corneal arcus had both higher LDL levels and higher CAC score tertiles [5].…”
Section: Cardiovascular Calcification and Lipids And Lipoproteinsmentioning
confidence: 93%
“…Indeed, we recently found that specific combinations, such as the presence of calcifications, LRNC, and IPH, are more frequently seen in male patients. 49 This suggests that having a carotid plaque with multiple vulnerable plaque features could signify an even higher stroke risk and that new studies are needed to show whether these kind of plaques are indeed more prone to rupture.…”
Section: Sex Differences In Carotid Plaque Characteristicsmentioning
confidence: 99%